The Role of EFL/ESL Teachers’ Psychological Empowerment and Optimism on Their Job Commitment - Xiong, Xiaoqin (Frontiers in Psychology, 2022)
Research has approved that teaching is a complex profession involving many cognitive, social, cultural, and psycho-emotional factors. To perform efficiently, teachers must be psycho-emotionally powerful and ready to cope with the existing challenges and complications of teaching a second/foreign language. This demands attempts to be made to psychologically empower the teachers to form positive outlooks about their profession and practices. Despite the criticality of psychological empowerment, few studies in L2 contexts have dealt with it. Against this gap, the present article aimed to theoretically analyze the interaction among teachers’ psychological empowerment, optimism, and commitment. In so doing, the definitions, models, components, typologies, and empirical studies related to these constructs were presented. Finally, practical implications of this line of research for EFL/ESL teachers, teacher trainers, and researchers are provided to raise their awareness of psycho-emotional factors involved L2 education.